Educational Paradigm of Academic Writing - L. V. Dudnik; T. S. Putilovskaya (Высшее образование в России)
The article reveals the concept of academic writing educational paradigm, which is made up of several different didactic aspects to be taken into account in planning and organising the learning process. The aim of the article is to make an overview of these aspects in order to show how academic writing can be incorporated in the existing higher educational curricula, in particular the foreign language course, and to design an effective didactic mechanism of academic writing acquisition. The authors formulate the major principles of organising and implementing the training process, the most important being the competence-and-activity-based approach to teaching, relying on the competence-based model of academic writing worked out by the authors and applying the step-bystep strategy of training. Regarding academic writing as a long process of knowledge, abilities and skills acquisition in which further development always relies on previous achievements allows the authors to presuppose that there are certain corner stones on the way to academic writing competence formation. These are writing a scientific essay, writing a synopsis and writing a research article, which are sequential elements of the paradigm. Correspondingly, the competence in research article writing can be acquired successfully on the basis of similar verbal activities which have very close competence-based patterns. This supposition is confirmed by the results of the experiment in which the students failed to write a research article without special training and wrote a scientific essay instead because they could rely on the skill of essay writing available in their verbal experience. The analysis carried out by the authors allows them to conclude that the way to academic writing, which is rather long and complicated, requires profound understanding of its educational paradigm for implementing the training process within the framework of the higher educational foreign language course.